EDUKASI DAN PENDAMPINGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA CLEANING SERVICE KLINIK PRATAMA DI DENPASAR - Putu Nita Cahyawati; Ni Kadek Elmy Saniathi (UNHI Press, 2022)
Coronavirus Disease-2019 was first discovered in Indonesia on March 2, 2020. The Government of Indonesia is taking various strategic steps to prevent and handle this case. The government emphasizes preventive measures by implementing health protocols and clean and healthy living behaviors starting from the individual and family levels. This activity aims to provide education and assistance to cleaning services in implementing clean and healthy living behaviors, especially when working. The activities began with discussion sessions, pretest, education process, and posttest. As a result, we found that the percentage of partners' attendance and participation in this activity was very good, namely 100%. This result is following the target set. The educational process can increase the knowledge of partners. This is indicated by an increase in the pretest and posttest scores from 51.5 to 84 points, with an average value of 84 points. Based on the results of monitoring in the form of direct observations, partners have implemented protocols for the use of adequate personal protective equipment while working. Based on this data, it can be concluded that the provision of education and assistance can increase the knowledge and behavior of partners in implementing clean and healthy living behaviors.